2020
DOI: 10.4250/jcvi.2020.0025
|View full text |Cite
|
Sign up to set email alerts
|

Changes in QRS Duration Are Associated with a Therapeutic Response to Sacubitril–valsartan in Heart Failure with Reduced Ejection Fraction

Abstract: BACKGROUND: Recent studies have demonstrated that angiotensin receptor neprilysin inhibitors (ARNIs) can reverse the cardiac remodeling effects that occur in heart failure with reduced ejection fraction (HFrEF). These studies have also suggested that ARNIs have favorable effects on ventricular dyssynchrony. We assessed the changes in QRS duration associated with ARNIs in patients with HFrEF. METHODS: We retrospectively investigated patients with HFrEF (defined by a left ventricular ejection fraction [LVEF] ≤ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our findings suggest that QRS duration is negatively correlated with LVEF in patients with LBBB. QRS duration also appears to be a reflection of LV ejection fraction, in line with the study by Kim and colleagues 16 . A study of 23 patients with normal conduction and 12 patients with complete LBBB reported that patients with complete LBBB had higher end-systolic and diastolic volumes and a lower EF than patients with normal conduction 17 .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings suggest that QRS duration is negatively correlated with LVEF in patients with LBBB. QRS duration also appears to be a reflection of LV ejection fraction, in line with the study by Kim and colleagues 16 . A study of 23 patients with normal conduction and 12 patients with complete LBBB reported that patients with complete LBBB had higher end-systolic and diastolic volumes and a lower EF than patients with normal conduction 17 .…”
Section: Discussionsupporting
confidence: 87%
“…18 Shorter QRS durations, which reflect favorable cardiac reverse remodeling processes and LV synchrony, may be associated with responses to ARNIs in patients with HFrEF, compared with non-QRS shortening. 19 Besides, greater LVEF is achieved with earlier initiation of GDMT in patients with HF duration <1 year, compared with those with !1 year. 8 In our study, we also found different alterations in the electrophysiological parameters after sacubitril/valsartan therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Larger left ventricular volumes were also found to be associated with QRS width as well as Q-waves after anterior MI and was inversely associated with LVEF 37 . The potential for better LV-recovery in HFrEF treated with ARNIs was described to be better in patients with shorter QRS complex 38 . Our analysis did not identify any significant associations of LV-volumes and LV-diameters with baseline QRS width.…”
Section: Discussionmentioning
confidence: 99%